2021
DOI: 10.1016/j.carbpol.2020.117042
|View full text |Cite
|
Sign up to set email alerts
|

Inulin from Pachyrhizus erosus root and its production intensification using evolutionary algorithm approach and response surface methodology

Abstract: Highlights The ultrasound assisted extraction of inulin from Pachyrhizus erosus roots. Compared with microwave assisted and conventional extraction technique. Optimization the extraction by RSM and genetic algorithm. Purity profiling and degree of polymerization of extracted inulin. Significant prebiotic activity recorded using Lactobacillus fermentum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
10
2
Order By: Relevance
“…It can be roughly estimated that the inulin content in the yam bean tuber extract was at approximately 5%. This was relatively lower than those reported earlier by Sarkar et al (2021) in which the percent (%) yield of inulin obtained from the yam bean tubers by using the conventional hot water extraction was at about 10%. 4 However, various factors may influence the inulin content in the yam bean tubers including plant variety, planting condition, harvest time, nutritional status as well as the extraction methods.…”
Section: Carbohydrate Content Assaycontrasting
confidence: 73%
See 2 more Smart Citations
“…It can be roughly estimated that the inulin content in the yam bean tuber extract was at approximately 5%. This was relatively lower than those reported earlier by Sarkar et al (2021) in which the percent (%) yield of inulin obtained from the yam bean tubers by using the conventional hot water extraction was at about 10%. 4 However, various factors may influence the inulin content in the yam bean tubers including plant variety, planting condition, harvest time, nutritional status as well as the extraction methods.…”
Section: Carbohydrate Content Assaycontrasting
confidence: 73%
“…This was relatively lower than those reported earlier by Sarkar et al (2021) in which the percent (%) yield of inulin obtained from the yam bean tubers by using the conventional hot water extraction was at about 10%. 4 However, various factors may influence the inulin content in the yam bean tubers including plant variety, planting condition, harvest time, nutritional status as well as the extraction methods. The percent (%) yield of inulin obtained from the tubers of yam bean is relatively lower than those achieved from tuberous roots of Jerusalem artichoke (Helianthus tuberosus L.) or chicory (Cynara scolymnus L.) reported earlier.…”
Section: Carbohydrate Content Assaycontrasting
confidence: 73%
See 1 more Smart Citation
“…Disintegration patterns in samples were different after UAE and MAE. The high yield of target compounds after UAE and MAE methods is attributed to the disruption of cellular structure followed by better penetration of solvent inside the matrix with acoustic cavitation/enhanced temperature (Sarkar et al, 2021).…”
Section: Surface Morphology Of Processed Pineapple Wastementioning
confidence: 99%
“…Jicama polysaccharides include starch (Buckman et al, 2018;González et al, 2018;Melo et al, 2003), pectin, cellulose, xyloglucans, heteromannans, heteroxylans (Klockeman et al, 1991;Noman et al, 2007;Ramos de la Peña et al, 2013) and, in much lower quantities, inulin (Stevenson et al, 2007), which could be the fiber material that has been related to the nutraceutical beneficial effects. There are just a few recent studies confirming the presence of fructooligosaccharides: Sarkar et al (2021) cited its presence in jicama powder, confirmed through its fructose and glucose content. However, we did not find any investigations that present an HPLC methodology for inulin or fructooligosaccharides detection.…”
Section: Introductionmentioning
confidence: 99%